Unlocking torts - Dua, Sanmeet; Turner, Chris (Milton Park, Abingdon, Oxon [UK] : Routledge, 2014)
"The law of torts is a vibrant and fast-moving area of the legal system.Unlocking Torts will ensure that you grasp the main concepts with ease providing you with an essential foundation to tort law. The book explains in detailed, yet straightforward, terms: the origins of tortious liability torts and goods trespass to the person defamation the many aspects of negligence economic torts trespass to land breaches of statutory duty nuisance employers' liability; vicarious liability liability for land and animals remedies and limitations. This fourth edition is fully up-to-date with the latest developments in the law and now includes all significant new cases plus an extended section on privacy. The Unlocking the Law series is designed specifically to make the law accessible. Each chapter opens with a list of aims and objectives, contains activities such as quick quizzes and self-test questions, key facts charts to consolidate your knowledge, and diagrams to aid learning. Cases and judgments are prominently displayed, as are primary source quotations. Summaries help check your understanding of each chapter, there is a glossary of legal terminology. New features include problem questions with guidance on answering, as well as essay questions and answer plans, plus cases and materials exercises. All titles in the series follow the same formula and include the same features so students can move easily from one subject to another. The series covers all the core subjects required by the Bar Council and the Law Society for entry onto professional qualifications as well as popular option units. The popular website www.unlockingthelaw.co.uk has been improved and updated. It provides free resources such as multiple choice questions, key questions and answers, revision mp3s and cases and materials exercises"--
"The law of torts is a vibrant and fast-moving area of the legal system.Unlocking Torts will ensure that you grasp the main concepts with ease providing you with an essential foundation to tort law. The book explains in detailed, yet straightforward, terms: the origins of tortious liability torts and goods trespass to the person defamation the many aspects of negligence economic torts trespass to land breaches of statutory duty nuisance employers' liability; vicarious liability liability for land and animals remedies and limitations. This fourth edition is fully up-to-date with the latest developments in the law and now includes all significant new cases plus an extended section on privacy"--
Includes bibliographical references and index.
Description based on print version record cip data provided by publisher.
Keywords: Torts -- Great Britain; Torts -- Great Britain -- Cases; LAW / General